Analisis Perilaku Pembelian Konsumen Ayam Kampung (Gallus Domesticus) di Kota Kendari (Studi Kasus pada Konsumen di Pasar Basah “Mall Mandonga”) - Irma Irma; Bahari Bahari; Weka Gusmiarty Abdullah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research aims to analyze: (1) types of purchasing behavior of free-range chicken consumers in Kendari City, (2) factors that influence the purchasing decisions of free-range chicken consumers. The factors studied in this research are cultural, social, personal, psychological factors, chicken price, age and income. Determining the location of this research was carried out purposively. This research was conducted at the Wet Market (Mandonga Mall) Kendari City with the data used being primary and secondary data. This research used 35 respondents each who bought free-range chickens and those who did not buy free-range chickens taken using accidental sampling. The data analysis used in this research is engagement inventory design analysis and logistic regression analysis. The results of this research indicate that the type of consumer purchasing behavior is classified as a complex purchasing behavior type. This type of behavior has a high level of involvement in decision making to purchase free-range chicken and consumers are aware of the real differences between attributes. Factors that have a positive influence on consumer purchasing decisions are cultural, psychological and age variables. Variables that have a negative influence on purchasing decisions are social factors and income. Factors that have no influence are price and personal variables.